EFEKTIVITAS PENGGUNAAN MEDIA BUKU CERITA BERGAMBAR DALAM MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS 3 DI MI AN-NIDHOM KEBONREJO GENTENG - Ramiati, Eka; Mashuri, Imam; Safitri, Dewi (INCARE, International Journal of Educational Resources, 2021)
The aim of this study; 1) knowing the use of pictorial storybook media in improving social studies learning outcomes for 3rd grade students in MI An- Nidhom Kebonrejo Genteng, Banyuwangi Regency, 2) Analyzing the effectiveness of using picture books in improving social studies learning outcomes for 3rd grade students in MI An-Nidhom Kebonrejo Genteng, Banyuwangi Regency. This type of research is a quantitative descriptive Quasi Experiment model with the One-Shot Case study research approach. Validation of this research with Kolmogorov Smirnov's validity and reliability testing technique. Whereas in the data analysis used using statistical hypothesis with analysis Chi Square and the partial hypothesis test (t test), the calculation uses SPSS 16 For Windows 7. The results showed that 1) The development of illustrated storybooks used in social studies theme of enthusiasm for work was seen from the cover of storybooks, storybook contents and anatomy of storybooks said to be feasible, with the results of the questionnaire obtained a low score of 4 students (9.30%) 34 students (79.07%) and got a high score of 5 students (11.63%). 2) Effectiveness of the use of illustrated storybook media on social studies learning outcomes in grade 3 obtained tcount of 5.891 with a significance value of 0.420 greater than 0.102 (0.420> 0.102), and the regression coefficient has a positive value of 0.309; then the hypothesis which states that "effective illustrated storybooks in improving the results of social studies learning for 3rd grade students in MI An-Nidhom Kebonrejo, Genteng District, Banyuwangi Regency" is accepted.